Factors affecting the knowledge levels, awareness, attitudes, and behaviors of family physicians about child abuse and neglect in Turkiye and changes in them with the training provided - Muhammet Bayraktar; Serdar Deniz; Elçin Balcı; Rifat Güveli; Abdullah Bircan (Frontiers in Public Health, 2025)
IntroductionThis study aimed to determine family physicians’ attitudes, behaviors, and levels of knowledge about child abuse and neglect (CAaN) and examine changes through in-service training provided by academics who have studies on the subject.Materials and methodsThis cross-sectional and intervention-type study was conducted between September and December 2017 with the required permissions taken. All family physicians working in 116 family medicine units in family health centers in Niğde province were included in the study. It was conducted in two stages, using survey forms before and after the education given to the participants. The study was completed with 96 family physicians.ResultsThe mean age of the physicians participating in the study was 40.2 ± 7.84 years. Thirty-five (36.5%) were female, 85 (88.5%) were married, and 75 (78.1%) had children. They have been practicing medicine for 15.1 ± 7.81 years, and 90 (93.8%) are general practitioners. Eighty-eight (91.7%) expressed that they give special importance to signs of neglect and abuse in children brought in for examination. Thirty-one (32.3%) stated that they have encountered signs of neglect and/ or abuse in children during their professional lives, and 8 (8.3%) have encountered signs of abuse and/or neglect in the last year. Fifty-five (57.3%) received training on CAaN during their education at medical school, and 72 (75.0%) received in-service training on CAaN after they started working as physicians. Eighty-two (85.4%) stated that if training were to be organized on CAaN, would want to attend to receive information on the subject and increase/ renew their knowledge, and 88 (91.7%) stated that they would like to be informed about the results of the study. The changes in the scale subcategories’ mean scores and the general mean scores of the scale in the pre-test administered before the training and the post-test administered after the training show that the participants had a development between the two applications to have sufficient knowledge about the subject with the training, statistically significantly (p < 0.05).ConclusionIn-service training given to family physicians has positive effects on the detection of CAaN. Awareness and knowledge levels should be maintained with regular in-service trainings.